Prophets and people of the Semitic religion in English translated Quran: Corpus and CDA over western power dominance - Farah, Rafika Rabba; Sumarsono, Puji; ., Sukarma (Universitas Islam Negeri Banda Aceh, 2022)
The Quran is the oldest scripture revealed by Allah to the Prophet Muhammad (peace be upon Him), and its originality has been preserved to this day, as evidenced by the language it employs—Arabic. It has become a popular reference for Muslims and non-Muslims alike, especially since the 9/11 tragedy. Not surprisingly, its native text, Arabic, is now widely available in translated versions, with English-translated Quran being the most frequent. The current study intends to investigate the meta-religious text concerning Prophets and the people mentioned in the Quran. The primary data of this study were obtained from the English-translated Quran by Talal Itani and analyzed with qualitative analysis software, NVivo 12 Plus, using the text search and query feature. Following that, discourse analysis was used to examine the text, social cognition, and sociocultural context. The results indicate that Moses ranked first in the Prophets category with 135 references, while the other prophets had a varied distribution: Abraham had 72, Jesus had 25, and Muhammad had 12 references. People of Israel were the most frequently discovered words with 42 mentions, followed by Jew, Christian, and Muslim. This research reveals surprising discursive evidence showing Muhammad and Muslims were the lowest of all categories. This means that the Quran is a revelation that is aimed not only for Muslims but also for all humanities, particularly the other Semitic religions: Christianity and Judaism.